Notoginsenoside R1–Induced Neuronal Repair in Models of Alzheimer Disease Is Associated With an Alteration in Neuronal Hyperexcitability, Which Is Regulated by Nav - Hu, Tao; Li, Shan; Liang, Wen-Qi; Li, Shan-Shan; Lu, Min-Nan; Chen, Bo; Zhang, Li; Mao, Rui; Ding, Wan-Hai; Gao, Wen-Wei; Chen, Shi-Wen; XiYang, Yan-Bin; et al. (Frontiers in Cellular Neuroscience, 2020)
Alzheimer disease is characterized by a progressive cognitive deficit and may be associated with an aberrant hyperexcitability of the neuronal network. Notoginsenoside R1 (R1), a major activity ingredient from Panax notoginseng, has demonstrated favorable changes in neuronal plasticity and induced neuroprotective effects in brain injuries, resulting from various disorders, however, the underlying mechanisms are still not well understood. In the present study, we aimed to explore the possible neuroprotective effects induced by R1 in a mouse model of AD and the mechanisms underlying these effects. Treatment with R1 significantly improved learning and memory functions and redressed neuronal hyperexcitability in amyloid precursor protein/presenilin-1 mice by altering the numbers and/or distribution of the members of voltage-gated sodium channels (Nav). Moreover, we determined whether R1 contributed to the regulation of neuronal excitability in Aβ-42–injured cells. Results of our study demonstrated that treatment with R1 rescued Aβ1-42–induced injured neurons by increasing cell viability. R1-induced alleviation in neuronal hyperexcitability might be associated with reduced Navβ2 cleavage, which partially reversed the abnormal distribution of Nav1.1α. These results suggested that R1 played a vital role in the recovery of Aβ1-42–induced neuronal injury and hyperexcitability, which is regulated by Nav proteins. Therefore, R1 may be a promising candidate in the treatment of AD.